Pertumbuhan Planlet Lidah Mertua (Sansevieria sp.) Blue Leaf dari Kultur Kalus - Diah Ratnadewi; Ai Nurhasanah Husnul Izzati; Aris Tjahjoleksono (Departemen Biologi, Institut Pertanian Bogor, 2015)
Lidah mertua (Sansevieria sp.) Blue Leaf is a slow growing ornamental plant. It is also difficult to reproduce. Therefore market demands for this plant is impossible to fulfill through conventional methods of propagation such as leaf cutting or layering. Tissue culture is one of the alternatives to solve the problem of plant propagation. In vitro culture of Sansevieria calli was induced for shooting, and rooting afterwards. The basic media of WP was superior than MS in producing multiple shoots, and this WP media containing of BAP 5 mg/L and NAA 0,5 mg/L (WH1) gave the highest number of shoots and leaves on plantlets, as well as the best growth performance. The shoots started to appear two weeks after culture. Plantlets from WH1 rooted in higher frequency as well on rooting media. A mixture of compost, sand, and zeolit (4:4:1) enriched with a nutritive solution, composting of 1⁄4 WP plus IBA 0.5 mg/L, was a poreous media that was able to induce rooting of this plant.